Employment trajectories of workers in low-skilled jobs in Western Germany - Arthur Kaboth; Lena Hünefeld; Ralf K. Himmelreicher (Journal for Labour Market Research, 2023)
According to the segmentation theory, low-skilled jobs belong to the secondary sector of the labour market. Low-skilled jobs do not require vocational training and workers are interchangeable. Therefore, workers in this sector have poor working conditions and are regularly affected by employment interruptions. The current state of research, however, does not provide any longitudinal information about individual employment stability of workers performing low-skilled jobs. Furthermore, most of these workers are employed full-time and have completed professional training. Against this background, this paper deals with employment trajectories of workers in low-skilled jobs and their changes over time with regard to standard employment relationship. The aim of the explorative study is to analyse the assignment of workers in low-skilled jobs within the segmentation theory and to determine how segments have changed over time. We use data from the German Socio-Economic Panel (GSOEP) to analyse the employment trajectories of two cohorts aged 35 to 44 years in Western Germany over a period of ten years. The employment trajectories are compared by means of sequence analysis with optimal matching algorithm as well as cluster analysis applying the 'Partitioning Around Medoids' method (PAM) in combination with results from hierarchical ward clusters. The employment trajectories indicate that low-skilled jobs can be assigned to both the secondary and the primary sectors. The cohort comparison of employment trajectories shows change and continuity in the context of segments.
Keywords: C38; J42; J62; 330; Low-skilled jobs; Employment trajectories; Standard employment; Segmentation theory; Sequence andcluster analysis